MEMS very low capacitive pressure sensor based on CMOS process - Muhamad Ramdzan Buyong,; Norazreen Abd Aziz,; Burhanuddin Yeop Majlis, (Universiti Kebangsaan Malaysia, 2011)
The CMOS standard process with advantage of simplicity in term of design and fabrication process compatibility has triggered the invention of MEMS very low capacitive pressure sensor, (MEMS-VLCPS). In this paper the development of the whole structure of MEMS-VLCPS that involves the design simulation, fabrication and testing is described. The novelty of this work lies in the design and fabrication process itself. A new technique in fabricating thin sensor membrane of VLCPS using seal-off techniques is also presented. The physical structure of the membrane consists of parallel plate. The top plate acts as the flexible electrode membrane and the bottom plate acts as the counter electrode membrane. Both plates are separated by absolute air gap with fixed end at both sides. As a result, it was found that the etch-opening holes of 0.8 μm and seal-off thickness of 4000 Å gave the optimum sealing surface. The percentage of relative capacitance change is extracted from the reference capacitance measurement. Air gap thickness of 0.3 μm gives the highest percentage of PRCC showing that smaller air gap thickness provides a larger change in capacitance value